Assessing the Nexus between ICT Intensity, Productivity, Employment and Output in South Africa’s Agro-processing Industries - M. H. Lefophane; Mmatlou Kalaba (New Advances in Business, Management and Economics Vol. 4, 2025)
This chapter explores the nexus between ICT intensity and growth of South Africa’s agro-processing industries using data from 1994 to 2017. To do so, the ICT intensity index was used to calculate the ICT intensity of 10 agro-processing industries. Afterwards, the growth rates of labour productivity, output, and employment were computed. Ultimately, the Toda and Yamamoto (TY) Granger non-causality test was applied to examine the causal relationship between ICT intensity and growth of labour productivity, output, and employment. The TY test proved that causality occurs in line with ICT intensity, such that evidence of causality was detected for an industry that has invested more highly in ICT. This implies that the growth performance of the agro-processing industries could be transformed (enhanced) through an increase in ICT investment.